2016
DOI: 10.1007/s11548-016-1486-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative navigation in complex head and neck resections: indications and limits

Abstract: Intraoperative navigation resulted to be a reliable method to improve oncological safety in a selected group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…The main limitation of the present study is its preclinical nature, which makes the results potentially biased by the "ideal" conditions of the laboratory setting. However, the preliminary clinical data published in the literature so far align with the observations of the present study [21][22][23]. This makes the translation of such technology into clinical practice a step forward, however there must be adequate research in the clinical setting to ensure that there is measurable clinical benefit to the patient from an oncological point of view.…”
Section: Limitations Of the Studysupporting
confidence: 75%
See 2 more Smart Citations
“…The main limitation of the present study is its preclinical nature, which makes the results potentially biased by the "ideal" conditions of the laboratory setting. However, the preliminary clinical data published in the literature so far align with the observations of the present study [21][22][23]. This makes the translation of such technology into clinical practice a step forward, however there must be adequate research in the clinical setting to ensure that there is measurable clinical benefit to the patient from an oncological point of view.…”
Section: Limitations Of the Studysupporting
confidence: 75%
“…Likewise, Catanzaro et al and Tarsitano et al recently demonstrated that navigation provided a significant improvement in terms of deep margin status when added to the standard procedure for advanced maxillary, oral, or orbital cancers (i.e. ablation followed by mapping of the surgical bed with frozen-section biopsies) [21,22]. While these studies included only a limited number of patients (18), they were the first advocates for margin improvement using surgical navigation.…”
Section: Surgical Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the highest overall inadequate margins rates (15%-30%) in all of surgical oncology are found in head and neck cancer (6). Despite the introduction of many novel technologies, inadequate margin rates have not changed over the past 30 years as surgeons cannot successfully differentiate healthy from diseased tissue (6,7). The most commonly used method for intraoperative margin control is frozen section analysis (FSA); however, this technique suffers from sampling errors as surgeons often struggle to identify which suspicious regions should be sent for histopathologic assessment (8).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection remains the gold standard for the majority of solid tumors [1]. Despite improved medical technologies for preoperative surgical planning [2,3] and intraoperative guidance, including radio-guided and fluorescence imaging-based approaches [4,5], head and neck surgeons still primarily rely on their vision and palpation to determine surgical margins. Not surprisingly, tumor-positive margins are still found in 15–30% of all head and neck cancer resections [68].…”
Section: Introductionmentioning
confidence: 99%